Domestic Inquiries in Malaysia: Procedural Fairness, Challenges and Best Practices for Workplace Discipline - ismail, fadillah; Mohd Rosli, Nur Amalina (Human Sustainability Procedia, 2025)
This paper examines the domestic inquiry (DI) process as a critical procedural mechanism for enforcing workplace discipline and upholding principles of natural justice within Malaysia’s employment context. Anchored in Section 14 of the Employment Act 1955, DI serves as a legal safeguard to ensure fairness and equity in addressing employee misconduct and disciplinary actions. The paper outlines the key steps of a well-conducted domestic inquiry—from the issuance of show cause letters to the hearing, deliberation, and appeal—emphasizing procedural fairness, impartiality, and documentation as fundamental pillars. It also explores the main triggers of DIs, such as violations of company policies, breach of contract terms, negligence, and workplace fraud. Comparative references to best practices from the United Kingdom and Australia highlight Malaysia’s procedural gaps and the need for legal clarity. Despite legal frameworks being in place, challenges persist due to inconsistencies in implementation, lack of training, poor record-keeping, and the absence of standardized inquiry protocols. The study recommends structured reforms, including enhanced training for HR personnel, improved documentation systems, clearer policies, and regular reviews of DI procedures to ensure legal compliance and organizational integrity. Ultimately, a robust and transparent domestic inquiry system is essential not only for minimizing legal risks and wrongful dismissal claims but also for reinforcing organizational trust, governance, and employee morale.